Implementation of Guidance and Counseling at schools - Rosmawati, Rosmawati; Donal, Donal (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of this study was: a) implementation of guidance and counseling at schools, b) Suitability between workload and implementation, c) Barriers encountered by guidance and counseling teachers in the implementation of services, d) Changes and progress of students after being given guidanceand counseling services. Thisresearch was descriptive qualitative research. The population of this study were the teachers of guidance and counseling at junior high schools, boarding school, senior high schools and vocational schools in Pekanbaru. This research used random sampling. This research was concluded that counselor or guidance and counseling teachers at the schools had implemented, among others: a) preparing guidance and counseling programs, b) Implementing guidance and counseling programs, c) Carry out evaluations, and follow-up. Implementation of guidance and counseling at schools was not appropriate between workload and implementation. This is reflected in the performance of the guidance and counseling teachers in carrying out 16 hours a week or 66% of the workload of carrying out the guidance and counseling supposed. Lack of time providing basic services, responsive services, specialization services and system support so that occured the implementation of guidance and counseling services at schools. The implementation of guidance and counseling at school helps the students in solving their problems and develops themselves according to their talents and interests. It was a changed and progress obtained by students after being given guidance and counseling services at school.